Advanced structural internationalization of Universities is unethical. (November 2021) - Turcan, Romeo V; Juho, Anita; Reilly, John E
In this 'Speaking Out' paper, we challenge contemporary orthodoxies in the field of 'advanced structural' internationalization of universities by focusing on significant, but neglected issues and challenges which arise from the current substantive developments in this field. By referring to 'advanced structural' internationalization, we want to distinguish between what might be broadly defined as internationalization at home and internationalization abroad, which we consider 'structural'. 'Advanced structural' precisely because it involves transporting and re-engineering relations with governments, partners, students and other stakeholders and tends to be high risk, high commitment, and high cost. We 'look' at 'advanced structural' internationalization through the theoretical lenses of university autonomy. Since there is limited research at the intersection of international business and university autonomy, along with our experience, we draw on publicly available data relating to issues and challenges which arise from the pursuit of 'advanced structural' internationalization in higher education to construct an analytical narrative and ethical discourse appropriate to the radically changing structural, theoretical, and ideological realities we now face in this field. 'Advanced structural' internationalization poses serious ethical questions, which suggest that it does not have strong ethical foundations. In this conclusion, we are influenced by the degree of difference between university autonomy settings at home and the operation in the host country. The greater the disparity the more it is likely that the standards and practices which would be applied in the home environment fail to apply in the host. Hence, our thesis: 'advanced structural' internationalization of universities is unethical.